Perbedaan Kepuasan Pelanggan Pada Koperasi di Palembang - ratnawati, Ratnawati; Nurrrahmi, Maftuhah (Universitas muhammadiyah palembang, 2011)
This study aims to determine differences in costomer satifaction at koperasi Dharma Karya koperasi wanita petra and Koperasi Kredit Rukun Palembang. The result is expected to provide input and information about how strong costomer satifacationin the work of koperasi Dharma Karya, Koperasi Wanita Petra, and Koperasi Kredit Rukun Palembang. The population in this study is the costomers koperasi Dharma Karya, Koperasi Wanita Petra, and Koperasi Kredit Rukun Palembang. The method of sampling conducted on the basis of sample random samplingwith the assumption that the population have the same opportunitiesto be taken as asample. Data collection was done by distributing questionnaires to costomer Koperasi Dharma Karya, Koperasi Wanita Petra, and Koperasi Kredit Rukun Palembang sampled. For the there are differences in costomer satisfaction in koperasi Dharma Karya, Koperasi Wanita Petra, and Koperasi Kredit Rukun Palembang.